PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP KUALITAS PELAYANAN KEPADA PEMUSTAKA DI DINAS PERPUSTAKAAN DAN KEARSIPAN PAMEKASAN - Devi Lestari Pramita Putri; Siti Salama Amar (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
This study aims to determine effect of management information systems on service quality to users in the Pamekasan Library and Archives Service. Management information system (SIM) has three components namely usability, information quality, and interaction quality. This type of research is quantitative, the population in this study were all members of the Dinas Perpustakaan dan Kearsipan Pamekasan as many as 17,128 members. The sample used in this study were 99 members. Data analysis techniques in this study used multiple linear regression test, which firstly used statistical test using instrument test and classical assumption test. The conclusions of the results of this study indicate that partially the usability, information quality, and interaction quality have an influence on the quality of service while the use. And simultaneously (together) usability, information quality, and interaction quality have an influence on service quality.